2020
DOI: 10.14814/phy2.14321
|View full text |Cite
|
Sign up to set email alerts
|

Chronic vagal nerve stimulation has no effect on tachycardia‐induced heart failure progression or excitation–contraction coupling

Abstract: Autonomic dysregulation plays a key role in the development and progression of heart failure (HF). Vagal nerve stimulation (VNS) may be a promising therapeutic approach.However, the outcomes from clinical trials evaluating VNS in HF have been mixed, and the mechanisms underlying this treatment remain poorly understood. Intermittent How to cite this article: Radcliffe EJ, Pearman CM, Watkins A, et al. Chronic vagal nerve stimulation has no effect on tachycardia-induced heart failure progression or excitation-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 39 publications
2
8
0
Order By: Relevance
“…VNS was delivered during closed-loop or open-loop stimulation regimes (see Modes of VNS Delivery for more details). Importantly, these VNS parameters are similar to previous preclinical studies using VNS for cardiovascular control (Sachdeva et al, 2020; Plachta et al, 2013 & 2014; Yamakawa et al, 2014; Shinlapawittayatorn et al, 2013), and fall within clinically relevant stimulation ranges used in previous human trials using VNS for cardiovascular therapy (Anand et al, 2020; Table 1: Radcliffe et al, 2020).…”
Section: Methodssupporting
confidence: 78%
See 3 more Smart Citations
“…VNS was delivered during closed-loop or open-loop stimulation regimes (see Modes of VNS Delivery for more details). Importantly, these VNS parameters are similar to previous preclinical studies using VNS for cardiovascular control (Sachdeva et al, 2020; Plachta et al, 2013 & 2014; Yamakawa et al, 2014; Shinlapawittayatorn et al, 2013), and fall within clinically relevant stimulation ranges used in previous human trials using VNS for cardiovascular therapy (Anand et al, 2020; Table 1: Radcliffe et al, 2020).…”
Section: Methodssupporting
confidence: 78%
“…5C, Isch. + OL-VNS, magenta; open-loop VNS = 20% duty cycle, with a balanced amount of VNS compared to the closed-loop ANN-VNS paradigm, and parameters similar to previous human open-loop VNS studies: Anand et al, 2020; Table 1: Radcliffe et al, 2020; full 13-element feature vector shown in Supplemental Fig. S6B; experimental schematic: Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…5C , Isch. + OL-VNS, magenta; open-loop VNS = 20% duty cycle, with a balanced amount of VNS compared to the closed-loop ANN-VNS paradigm, and parameters similar to previous human open-loop VNS studies; Table 1 ( 52 , 53 ); full 13-element feature vector shown in fig. S6B; experimental schematic in Fig.…”
Section: Resultsmentioning
confidence: 99%